2013
DOI: 10.1155/2013/381670
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Variation Orders in Road Construction Projects in Sri Lanka

Abstract: One of the most important problems in the construction industry is variations. They occur in every construction project and the magnitude of these variations varies considerably from project to project. Hence, the variations orders bear great importance right from the inception to completion in the construction industry. Most of the road construction projects in Sri Lanka have experienced a large number of variation orders. The client had to spend more than what was initially estimated in most cases. Sometimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…Charoenngam et al [33] suggested a web-based change order management system that supports documentation, communication and integration between different team members in the change order workflow to manage change order procedure. Halwatura and Ranasinghe [34] proposed that increasing communication channels and hire professional planning staff would reduce occurrence of changing orders in projects. Msallam et al [35] proposed an administration system that could reduce variation orders in Jordanian highway projects.…”
Section: Contractual and Governmental Proceduresmentioning
confidence: 99%
“…Charoenngam et al [33] suggested a web-based change order management system that supports documentation, communication and integration between different team members in the change order workflow to manage change order procedure. Halwatura and Ranasinghe [34] proposed that increasing communication channels and hire professional planning staff would reduce occurrence of changing orders in projects. Msallam et al [35] proposed an administration system that could reduce variation orders in Jordanian highway projects.…”
Section: Contractual and Governmental Proceduresmentioning
confidence: 99%
“…Often, interpretation varies depending on the experience and preference of the individual party. The absence of clear guidelines and mutual agreement between parties involved regarding the assessment of construction delay will sometimes sparks a dispute amongst them [14].…”
Section: Extention Of Time (Eot)mentioning
confidence: 99%
“…It is an official document that states the changes made into the original agreement between the client and the contractor. When a variation order is created, it brings several negative effects to both the client and the contractor [14].…”
Section: Variation Order (Vo)mentioning
confidence: 99%
“…Other studies which have also found the above factors for causes for delays in other Asian countries include Kuwait (Koushki et al 2005), Indonesia (Wiguna and Scott, 2003), India (Doloi et al 2012), Sri Lanka (Halwatura and Ranasinghe, 2013), Egypt (Marzouk and El-Rasas, 2014) and Combodia (Santoso and Soeng, 2016). Wiguna and Scott (2003) and Santoso and Soeng (2016) also added weather conditions (or natural disasters) and litigations on substandard construction work to the main causes of delays.…”
Section: Introductionmentioning
confidence: 96%